2020
DOI: 10.1109/jtehm.2019.2943170
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Implantable Wireless and Batteryless Bladder Pressure Monitor System for Lower Urinary Tract Dysfunction

Abstract: Background: Closed-loop neuromodulation based on bladder pressure is an effective therapy for lower urinary tract dysfunction. The catheter-based cystometry normally used for bladder pressure measurement is not conducive to patient health because it will bring great mental stress to the patient and increase the risk of infection. Method: This paper designs and implements an implantable wireless and batteryless bladder pressure monitor system that monitors bladder storage in real time by implanting a miniature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Despite of the recent development in biodegradable pressure sensors, there are still some issues, such as sensitivity, operating range, and controllability of biodegradability, essentially to be improved for accurate pressure monitoring of various tissues and organs. In other words, regarding there are huge recent demands for healthcare and diagnosis of diseases in early stage through the pressure sensing of diverse tissues and organs, such as intracranial pressure [ 152 , 153 , 154 , 155 , 156 , 157 ], intraocular pressure [ 158 , 159 , 160 , 161 , 162 , 163 ], heartbeat [ 164 , 165 , 166 ], and bladder pressure [ 167 , 168 , 169 , 170 ], we expect that the high-performance biodegradable pressure sensors will be much more important for diverse biomedical applications in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the recent development in biodegradable pressure sensors, there are still some issues, such as sensitivity, operating range, and controllability of biodegradability, essentially to be improved for accurate pressure monitoring of various tissues and organs. In other words, regarding there are huge recent demands for healthcare and diagnosis of diseases in early stage through the pressure sensing of diverse tissues and organs, such as intracranial pressure [ 152 , 153 , 154 , 155 , 156 , 157 ], intraocular pressure [ 158 , 159 , 160 , 161 , 162 , 163 ], heartbeat [ 164 , 165 , 166 ], and bladder pressure [ 167 , 168 , 169 , 170 ], we expect that the high-performance biodegradable pressure sensors will be much more important for diverse biomedical applications in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A similar method was used to power an implant without a battery at the resonant frequency of 140 kHz via a rectangular coil wrapped around the device. The pressure data was transmitted by Bluetooth BLE after analog-to-digital conversion of pressure signals obtained by a commercial liquid pressure sensor [110]. Another example of a batteryless implantable bladder sensor had a flexible diaphragm that transduced pressure variations to capacitance changes [111].…”
Section: ) Cardiac Pressure Sensormentioning
confidence: 99%
“…Reproduced with permission. [240] Copyright 2020, IEEE. f) Images of the expandable and implantable bioelectronic complex for the urinary bladder.…”
Section: Intraocular Pressure Sensingmentioning
confidence: 99%
“…[14] The implantable bladder sensors with microsize have attracted great interest for chronic pressure monitoring. There are the implantable wireless monitoring system for bladder pressure (Figure 8e), [240] and the implantable pressure and acceleration sensor to measure the small-scale autonomous movements relevant to bladder physiology. [241] Jang et al reported an expandable and implantable bioelectronic complex for the urinary bladder (Figure 8f).…”
Section: Bladder Pressure Sensingmentioning
confidence: 99%